Search for supersymmetry using final states with muons, jets, and missing transverse momentum with the CMS detector in √ s = 7 TeV pp collisions - Lukyanenko, S.T.; Obikhod, T.V. (Вопросы атомной науки и техники, 2015)
The results of search for superparticles in final states with jets, muons and missing transverse energy are presented. The study is based on a data obtained in proton-proton collisions at √s = 7 TeV. They correspond to 4.36 fb⁻¹ of integrated luminosity collected with the CMS detector in 2011. mSUGRA/MSSM model built in generator PYTHIA6 was used for SUSY signal modeling. Two selection criteria for searching SUSY- manifesting were used. Background from Standard Model processes was estimated using the MADGRAPH and POWHEG generators. It is shown that with confidence level 95% the data are found to be in agreement with Standard Model expectations and new physics effects are not observed in ranges ETmiss >200 GeV and Meffinc >600 GeV.